Human-insect interactions - Govorushko, Sergey, 1955- (Boca Raton, FL : CRC Press, 2018)
A complete picture of insects, with part 1 on the beneficial aspects of insects (pollination, etc.), and part 2 on the negative aspects (insect pests, etc.).
part PART 1: Positive Aspects -- chapter 1 1 Ecosystem Services -- chapter 1 2 Use of Insects in Science -- chapter 1 3 Use of Insects in Medicine and the Cosmetics Industry -- chapter 1 4 Use of Insects in Technology (Insect Bionics) -- chapter 1 5 Commercial Use of Insects -- chapter 1 6 The Use of Insects as Food -- chapter 1 7 Use of Insects in Agriculture and Forestry -- chapter 1 8 Insects as a Form of Entertainment -- chapter 1 9 Other Uses of Insects -- chapter 1 10 Businesses Related to Insects -- chapter 1 11 Insects in Culture -- chapter 1 12 Insect Conservation -- part Part 2: Negative Aspects -- chapter 2 1 Insects as Pests -- chapter 2 2 Insects as Vectors of Plant Diseases -- chapter 2 3 Insects as Vectors of Disease in Animals and Humans -- chapter 2 4 Blood-sucking Insects and Ticks -- chapter 2 5 Venomous Insects and Arachnids -- chapter 2 6 Invasions of Insects -- chapter 2 7 Insect Allergy -- chapter Conclusion -- chapter References.
"A science publishers book."
Includes bibliographical references and indexes.
Keywords: Insects; Beneficial insects; Insect pests